Synthesis of Silica-Coated Magnetic Nanoparticles and Application in the Detection of Pathogenic Viruses. (15th July 2013) - Quy, Dao Van; Hieu, Nguyen Minh; Tra, Pham Thi; Nam, Nguyen Hoang; Hai, Nguyen Hoang; Thai Son, Nguyen; Nghia, Phan Tuan; Anh, Nguyen Thi Van; Hong, Tran Thi; Luong, Nguyen Hoang
Abstract : Magnetic Fe3 O4 nanoparticles were prepared by coprecipitation and then coated with silica. These Fe3 O4 /SiO2 nanoparticles consisted of a 10–15 nm magnetic core and a silica shell of 2–5 nm thickness. The superparamagnetic property of the Fe3 O4 /SiO2 particles with the magnetization of 42.5 emu/g was confirmed by vibrating sample magnetometer (VSM). We further optimized buffers with these Fe3 O4 /SiO2 nanoparticles to isolate genomic DNA of hepatitis virus type B (HBV) and of Epstein-Barr virus (EBV) for detection of the viruses based on polymerase chain reaction (PCR) amplification of a 434 bp fragment of S gene specific for HBV and 250 bp fragment of nuclear antigen encoding gene specific for EBV. The purification efficiency of DNA of both HBV and EBV using obtained Fe3 O4 /SiO2 nanoparticles was superior to that obtained with commercialized Fe3 O4 /SiO2 microparticles, as indicated by (i) brighter PCR-amplified bands for both HBV and EBV and (ii) higher sensitivity in PCR-based detection of EBV load (copies/mL). The time required for DNA isolation using Fe3 O4 /SiO2 nanoparticles was significantly reduced as the particles were attracted to magnets more quickly (15–20 s) than the commercialized microparticles (2-3 min).